Omeprazole Increases the Efficacy of Acyclovir Against Herpes Simplex Virus Type 1 and 2 - Michaelis, Martin; Kleinschmidt, Malte C.; Bojkova, Denisa; Rabenau, Holger F.; Wass, Mark N.; Cinatl Jr., Jindrich (Frontiers in Microbiology, 2019)
Omeprazole was shown to improve the anti-cancer effects of the nucleoside-analogue 5-fluorouracil. Here, we combined omeprazole with the antiviral nucleoside analogues ribavirin and acyclovir. Omeprazole did not affect the antiviral effects of ribavirin in non-toxic concentrations up to 80µg/mL but increased the acyclovir-mediated effects on herpes simplex virus 1 and 2 (HSV-1 and -2) replication in a dose-dependent manner. Omeprazole alone reduced HSV-1 and -2 titers (but not HSV-induced formation of cytopathogenic effects (CPE)) at concentrations 40µg/mL. However, it exerted substantially stronger effects on acyclovir activity and also increased acyclovir activity at lower concentrations that did not directly interfere with HSV replication. Omeprazole 80µg/mL caused a 10.8-fold (Vero cells) and 47.7-fold (HaCaT cells) decrease of the acyclovir concentrations that reduced HSV-1-induced CPE formation by 50% (IC50). In HSV-2-infected cells, omeprazole 80µg/mL reduced the acyclovir IC50 by 7.3- (Vero cells) and 12.9-fold (HaCaT cells). In HaCaT cells, omeprazole 80µg/mL reduced the HSV-1 titer in the presence of acyclovir 1µg/mL by 1.6x105-fold and the HSV-2 titer in the presence of acyclovir 2µg/mL by 9.2x103-fold. The proton pump inhibitors pantoprazole, rabeprazole, lansoprazole, and dexlansoprazole increased the antiviral effects of acyclovir in a similar fashion as omeprazole, indicating this to be a drug class effect. In conclusion, proton pump inhibitors increase the anti-HSV activity of acyclovir and are candidates for antiviral therapies in combination with acyclovir, in particular for topical preparations for the treatment of immunocompromised individuals who are more likely to suffer from severe complications.